Acute Onset Right Upper Limb Excruciating Pain and Weakness – A Mysterious Presentation of Ewing’s Sarcoma Solved by Fine Needle Aspiration Cytology - Haramohan Sahoo; Sonashree Sahoo (Current Medical Issues)
Ewing’s sarcoma is a tumor that most commonly arises from bony structures. These cases usually present to the department of orthopedics for pain at the site of origin. A gradually worsening pain that aggravates with activity and during the night is the usual symptom. Acute presentations are rare. Presentation to the department of neurology with weakness of limb is extremely uncommon. However, Ewing’s sarcoma is a malignant tumor and can spread out of the bone of origin to involve surrounding nerves. We present here a very unusual case of a 30-year-old female who presented to the department of neurology with a 7-day history of excruciating pain in the right upper limb and weakness of the right upper limb due to Ewing’s sarcoma. Fine needle aspiration cytology was crucial in this case to make a diagnosis.